Safe Horizon: Victim support service in New York - Milivojević Sanja K. (Temida)
This article contains analysis of history and development of the victim support movement in United States of America, with particular focus on New York City. The analysis includes the causes of establishment, the history of the victim support services as well as today’s situation in the movement for helping victims of crime. Specific part of the article is dedicated to Safe Horizon, victim support service in New York, and programs this organization, known also under old name - Victim Services, Inc., is running today.